2018
DOI: 10.1017/s0968565017000282
|View full text |Cite
|
Sign up to set email alerts
|

‘The whole art of war is reduced to money’: remittances, short-term credit and financial intermediation in Anglo-Dutch military finance, 1688–1713

Abstract: The literature on the financial revolution and the rise of the English fiscal-military state frequently gives the impression that a singular set of reforms emanating from the Glorious Revolution of 1688 changed the entire landscape of English army finances, allowing a fundamental shift from patchwork solutions based on short-term credit and managed through a system of wholesale venality to a solid system of long-term funded loans raised on an impersonal market. This article focuses on the crucial role that mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This becomes the company's input regarding the strategy that will be implemented. Buyers were more dependent on sellers who have long credit (Brandon, 2018), and also prices become sensitive in purchasing 6.…”
Section: Analysis Of External Environmental Factorsmentioning
confidence: 99%
“…This becomes the company's input regarding the strategy that will be implemented. Buyers were more dependent on sellers who have long credit (Brandon, 2018), and also prices become sensitive in purchasing 6.…”
Section: Analysis Of External Environmental Factorsmentioning
confidence: 99%
“…67 Pepijn Brandon has observed that early modern military finance in "times of exploding costs and permanent emergencies" relied both on domestic resources and on the "strength of commercial and financial networks abroad." 68 The Livonians certainly had well-established commercial ties throughout the Baltic, but, during the struggle of 1558-1561, these failed to yield meaningful aid.…”
Section: Livonian Mercenary Warfare and Fiscal Responsesmentioning
confidence: 99%
“…the introduction; Graham 2014, pp. 97–102; Brandon 2018). Likewise, scarcity of specie coins, as well as problems of obtaining the right denomination for a specific market, hindered long-distance transactions and market integration.…”
mentioning
confidence: 99%